Tinjauan Yuridis Perusahaan Induk Perbankan (Bank Holding Company) & Fungsi Holding Terhadap Kemandirian Yuridis Anak Perusahaan Perbankan Pada Perbankan Nasional (Studi Penerapan POJK 39/POJK.03/2017 Tentang Kepemilikan Tunggal) - Fontian Munzil (Jurnal Media Justitia Nusantara, 2018)
The national economic system is the financial system and all financial service activities that carry out the intermediary function for various productive activities in the national economy. The financial service sector supervision agency (OJK) is an independent institution in safeguarding national interests including regulating ownership in the financial services sector. A strong banking structure can be achieved by structuring the bank's ownership structure through a single ownership policy by consolidating and increasing the effectiveness of Bank supervision in a consolidated manner. One of the adjustments to the Bank's shareholding structure can be done by establishing a Banking Holding Company or holding function. This study aims to examine, first, what is the juridical review of the banking holding company and holding function of banking subsidiaries in national banking? Second, how far is the juridical independence of a banking subsidiary to a banking holding company?. The research used is a normative juridical method for secondary data, namely primary, secondary and tertiary legal materials. The library research stage is the activity of collecting primary legal material data in the scope, economics and finance of the banking holding company related to the juridical independence of banking subsidiaries. Research specifications are descriptive analysis to strengthen old theories or in order to construct new theories. All data obtained will be analyzed qualitatively juridically and presented systematically and scientifically in analytical descriptive. The study found that, the first bank holding company and the holding function have a very broad legal standing for the banking subsidiaries in the national banking sector in accordance with the POJK SPP which directly controls the business activities of the Bank's subsidiaries, second, Bank's subsidiaries have limitations to maintain juridical independence as a legal entity in the banking business within the control structure under the bank holding company or holding function.